DEVELOPING COUNTRIES CAN BENEFIT FROM FREE TRADE ZONES UNDER THE CHALLENGES OF THE ECONOMIC SYSTEM - Researcher: Ziad Sabah Ali; Zelal Zein Alia (American Journals, 2024)
Many countries have sought to establish free trade areas, as a result of their economic importance in diversifying sources of financial revenues, especially in rentier countries, in light of the trend towards the capitalist economy in light of what has been produced by economic globalization, in addition to that many countries have tended to establish trade areas to support their economy , Especially in the field of attracting foreign investments for these areas, using them to transfer modern technology, operate the national workers of the countries that have established those areas, and adopting their products in meeting the needs of the local market, as the idea of establishing free trade areas as a tool for development through the allocation of specific sites in which application is applied Various special laws and systems are characterized by exemptions and facilities that qualify them to be investment attractions to develop export industries and international trade exchanges.
Keywords: Economic Diversification, Revitalization of Financial Revenue Sources.